2017
DOI: 10.5551/jat.35824
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Post-disaster Evacuation on Incidence of Metabolic Syndrome

Abstract: Aim: After the Great East Japan Earthquake, over 160,000 residents near the Fukushima Daiichi Nuclear Power Plant were forced to evacuate due to a nuclear accident. Health problems in these evacuees have since become major issues. We examined the association between evacuation and incidence of metabolic syndrome (METS) among residents in Fukushima.Methods: We conducted a cohort study among residents aged 40–74 years without METS at the time of the disaster in Fukushima. Among 20,269 residents who met the inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 49 publications
(39 reference statements)
2
70
0
Order By: Relevance
“…However, residents tended to avoid going out because of fears of radioactive exposure after Fukushima Daiichi Nuclear Power Plant accident. In fact, the proportion of residents who exercised was lower following the accident, especially for residents in the evacuation zone 11) . Therefore, fear of radioactive exposure can potentially increase the risk for MetS by decreased physical activity.…”
Section: Advance Publication Journal Of Atherosclerosis and Thrombosimentioning
confidence: 95%
See 2 more Smart Citations
“…However, residents tended to avoid going out because of fears of radioactive exposure after Fukushima Daiichi Nuclear Power Plant accident. In fact, the proportion of residents who exercised was lower following the accident, especially for residents in the evacuation zone 11) . Therefore, fear of radioactive exposure can potentially increase the risk for MetS by decreased physical activity.…”
Section: Advance Publication Journal Of Atherosclerosis and Thrombosimentioning
confidence: 95%
“…Moreover, mental status is also associated with MetS [2][3][4] . In the Comprehensive Health Check of Fukushima Health Management Survey (FHMS), we showed that evacuation was associated with various health problems, including MetS [5][6][7][8][9][10][11] . Moreover, the Mental Health and Lifestyle Survey in FHMS reported changes in mental status and lifestyle factors following the disaster 12) .…”
Section: Definitions and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Many prior studies reported different incidences in MS from 3.1 to 22.9 per 1,000 person-years using different definition criteria for adults aged 40 years or older. [4][5][6][7] Regarding the incidence of MS per 1,000 person-years in young adults aged younger than 40, values of 11.7 for men and women aged 18-30 years 8 ; 13.3 for men and women aged 20-32 years 9 ; 12.0 for women aged 18-30 years 10 ; and 20.4 for black men and 24.9 for white men, and 27.9 for black women and 12.5 for white women aged 18-30 years 11 were reported in the United States using NCEP-ATP III criteria. In addition, Dreyfus et al reported a cumulative incidence of 24.8% in 2,534 African-American and white women aged 18-30 years during a 25-year follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported an increase in the prevalence of diseases, such as obesity and lifestylerelated diseases, in residents of evacuation areas within Fukushima prefecture. [12][13][14][15] This increase in disease prevalence could be partly attributed to the increase in stress due to environmental changes caused by moving into temporary housing, living in an evacuation site outside the local area, or disturbance in eating habits. [16][17][18][19] Thus, psychological stress has been considered to be associated with adverse health effects among residents of evacuation areas throughout Fukushima prefecture.…”
Section: Discussionmentioning
confidence: 99%